Comparative analysis of regionalism in Latin America and Asia-Pacific - Pizarro, Ramiro (ECLAC SantiagoCL, 1999)
Explores the differences and smilarities among the initiatives of regional economic cooperation , as they appear in the still scarce comparative studies on the subject.